Resistencia de la temperatura y salinidad en Poecilia reticulata Peters, 1859 - Giusto, Anabella; Gómez, Sergio E.; Cassar, Carolina; Ferriz, Ricardo A. (Bioikos – Título não-corrente, 1998)
THERMAL AND SALINITY RESISTANCE ON Poecilia reticulata PETERS, 1859. ln this work resistance to high temperature was studied using the criticai thermal maximum (CTM) technique, as function to the aclimatation temperature (Ta). Difference between sex and length are not significative. The relationship between variables is CTM = 30.6098. Ta 0.0877 with r= 0.9478. The resistance to salinity (S) was studied with the determination of LC50-96 h using resistance time (tR50) and dosification of mortality techniques. The relationship between tR50 and salinity is tR50 = 5.7468. S-9.4034 with r= -0.9329. The estimation of LC50 at96 h is 24.12 gr/1.